2020
DOI: 10.1186/s13041-020-00674-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bodily states of fear facilitates bias perception of fearful faces

Abstract: We investigated whether enhanced interoceptive bodily states of fear would facilitate recognition of the fearful faces. Participants performed an emotional judgment task after a bodily imagery task inside a functional magnetic resonance imaging scanner. In the bodily imagery task, participants were instructed to imagine feeling the bodily sensations of two specific somatotopic patterns: a fear-associated bodily sensation (FBS) or a disgust-associated bodily sensation (DBS). They were shown faces expressing var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Correspondingly, individuals with better interoceptive accuracy are sensitive to the emotions of others 31 . Moreover, enhancement of interoceptive bodily states of fear may facilitate the recognition of the fearful faces 32 . Altered emotional processing is reported across functional neurological disorders (including FSs) (for a review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, individuals with better interoceptive accuracy are sensitive to the emotions of others 31 . Moreover, enhancement of interoceptive bodily states of fear may facilitate the recognition of the fearful faces 32 . Altered emotional processing is reported across functional neurological disorders (including FSs) (for a review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation is in contrast with the previous finding that interoceptive inference around the chest area facilitated fear perception. In the previous study, interoceptive inferences regarding congruent bodily sensation patterns (an emphasis on sensations around the chest) enhanced the behavioral recognition of fearful faces and neural responses elicited by fearful faces [ 25 ]. This involvement of bodily sensations around the chest in the perception of fearful faces supported previous studies on the pivotal role of cardiac interoception in fear processing [ 1 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found increased brain activities in sgACC, cuneus, and fusiform gyrus and decreased brain activities in the PAG and middle temporal cortex constituting the default mode network. It has been well known that the amygdala is the key brain region in the processing of emotional facial expression [ 25 ]. However, we were not able to find the change of brain activities in the amygdala in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations